Experimental and numerical investigation of low velocity impact on hybrid short-fiber reinforced foam core sandwich panel. (December 2021) - Sharei, Alireza; Safarabadi, Majid; Mashhadi, Mahmoud M; Solut, Reza Souri; Haghighi-Yazdi, Mojtaba
This paper presents an experimental and numerical study of the low-velocity impact on foam core sandwich panels reinforced using hybrid short fibers. The foam cores were reinforced with carbon, aramid and carbon-aramid hybrid short fibers. The face-sheets were made of two layers of glass/epoxy, and foam cores were made of two-part polyurethane. In order to acquire the appropriate weight ratio between foam and short fibers, the weight percentage of 10% was chosen for short fibers. Comparing the experimental results proved that carbon, aramid, and carbon-aramid respectively had a better effect on increasing Young modulus by around 100 to 180 per cent. Before performing impact tests, indentation tests were conducted and based on the results for the parameter of impact energy, the value of 6 J was chosen. According to the results of impact tests and the maximum contact force, hybrid reinforced foam, aramid short fiber reinforced foam and carbon short fiber reinforced foam improved the properties respectively by 18 to 30 per cent in comparison to non-reinforced foam. Furthermore, numerical simulations were conducted via ABAQUS. After modeling face-sheet and foam separately, and verifying the results with experiments, the sandwich panel was modeled entirely while the simulation difference of 9.1% on average with the experiment results was concluded.